(untitled) (International Journal of Engineering Sciences & Management Research, 2015)
We propose a secure cloud storage scheme that addresses security, privacy, authentication issues in the cloud. We are providing anonymous authentication feature so that user who want to store data on cloud remains anonymous from the cloud and other user. It is attribute based access control scheme so user with valid set of attributes can access the data on cloud. For key generation and management we are using distributed approach. The key distribution centers are multiple which manages keys so it is distributed in nature. We are using homomorphic encryption scheme which uses paillier encryption algorithm which is asymmetric algorithm and for authentication we are using SHA-1.